Hypertension After Multiple Transfusions - S. Untario; R. H. T. Netty; B. Permono (Paediatrica Indonesiana, 1982)
Two patients are reported who developed hypertension with or without convulsions after receiving multiple blood transfusions. The pathogenesis of this complication of transfusion is briefly discussed.